ORAL ANTICOAGULANTS IN AMBULATORY AND IN-HOSPITAL TREATMENT OF PATIENTS WITH ATRIAL FIBRILLATION ASSOCIATED WITH HYPERTENSION, ISCHEMIC HEART DISEASE AND CHRONIC HEART FAILURE: DATA FROM HOSPITAL REGISTRY RECVASA-CLINIC - E. V. Stepina; M. M. Loukianov; M. A. Bichurina; E. N. Belova; E. V. Kudryashov; Ju. V. Uzkov; S. A. Boytsov (Столичная издательская компания, 2017)
Aim. To estimate the rate of oral anticoagulants (OAC) prescription, continuity of anticoagulant therapy in hospital and ambulatory stages along with treatment adherence in patients with atrial fibrillation (AF) associated with hypertension (HT), ischemic heart disease (IHD) and chronic heart failure (CHF) within the registry of cardiovascular diseases. Material and methods. The study included 285 patients with AF combined with HT, IHD and CHF from the hospital registry RECVASA-CLINIC (n=3696). The rate of OAC prescription was evaluated in ambulatory and in-hospital stages according to medical records. Out-patient treatment was estimated via phone contact in 250 participants that represented 96.2% of all survived patients during follow-up of 24.1Ѓ}5.9 months after discharge from hospital. Medical adherence was evaluated using Morisky-Green questionnaire. Results. Mean age of patients was 73.9Ѓ}10.0 years (male - 52.6), CHA2DS2-VASc and HAS-BLED score were estimated as 5.14Ѓ}1.50 и 1.59Ѓ}0.79, respectively. Contraindications to OAC treatment were registered in 34 (11.9%) patients. In pre-hospital stage patients with paroxysmal AF received OAK more rarely comparing to those with permanent and persistent AF (31.8%, 51.7 and 55%, respectively; р<0.05). The rate of OAC administration in pre-hospital stage, on discharge and after 24.1Ѓ}5.9 months follow-up period was 40.4%, 88.1% and 82%, respectively, whereas patients with previous stroke were prescribed OACs more frequently (in 49%, 92.5% and 83.7% of cases, respectively). Only 43% of study participants had good compliance to medical treatment (score of 4) according to Morisky-Green questionnaire. Conclusion. OACs were under prescribed in pre-hospital stage and after 2 years of follow-up in patients with AF combined with HT, IHD and CHF comparing with in-hospital period (40.4% and 82% vs 88.1%). Medical compliance according to Morisky-Green questionnaire was not enough (43%) in high-risk patients after discharge from hospital.